Synthesis, Biological Activity, and Molecular Docking Study of Xanthenol and Its Disproportionation Products as Anticancer and Antimalarial Agents - Pratama, Ardhya Ayu; Jumina, Jumina; Anwar, Chairil (UI Scholars Hub, 2024)
Xanthone and its derivatives are well known for their broad biological activities. This research aims to investigate the anticancer and antimalarial activities of synthesized xanthenol and xanthene compounds and to elucidate their mechanisms of action through molecular docking. The xanthenol compound was obtained through xanthone reduction with sodium triacetoxyborohydride, and xanthene synthesis was studied through three different reaction conditions: uncatalyzed and catalyzed by Lewis acid or Bronsted acid. The reduction reaction produced xanthenol in 30.50% yield, whereas the three reaction conditions produced xanthene and xanthone in 39.35–75.48% yield. An anticancer assay for Vero, WiDr, HeLa, and T47D cell lines was evaluated with a microculture tetrazolium assay, and an antimalarial activity test was examined using the heme polymerization inhibition method. The xanthene compound showed the lowest IC50 value (44 µg/mL) among the products in the T47D cell line. Meanwhile, the antimalarial assay showed that the xanthone compound could inhibit heme polymerization, with an IC50 value of 114 µg/mL. The molecular docking study revealed that the anticancer activity of xanthene occurred through the inhibition of the cyclooxygenase-2 (COX-2) enzyme, and the antimalarial activity of xanthone occurred through the inhibition of the Plasmodium falciparum lactate dehydrogenase enzyme. These results showed that xanthene and xanthone compounds are potential anticancer and antimalarial drugs, respectively.